Estimation of Genetic Diversity in Four Genetic Groups of Local Kurdish Chicken Using RAPD-PCR - Shaker, Ahmed; Ameen, Questan; Al-Obaidi, Rana; Arif, Sehand; Sleman, Sirwan; Nore, Beston; Hermiz, Hani; Kirkuki, Shahla; Al-Khatib, Taher (مجلة الانبار للعلوم البيطرية)
The current study conducted to detect the genetic diversity between four genetic groups of Kurdish local chicken using RAPD-PCR technique. Ten random markers used to amplified DNA were selected for genotyping the four lines. One hundred twenty four polymorphic bands were amplified, the bands size ranged between (2500 and 100 bp). The primer (OPA-05, OPA-18) produced maximum number of polymorphic bands, while primers named (OPA-16) produced minimum number of polymorphic bands. The (WNFS) genetic group showed the highest number of amplified fragments (55) for both male and female (30), (25) respectively. While (BBN) genetic group showed the lowest number of amplified fragments (20) for both male and female (7), (13) respectively. According to the results obtained from the current study, it can be conclude that the four genetic groups differ genetically. Moreover the results will help the breeders to study new selection strategies between the four genetic groups.